Khalifah Fatimiyah Di Mesir - Budi, Syah (Tasamuh: Jurnal Studi Islam, 2016)
This article describes more about the existence of the Fatimid Caliph. Caliph can be seen from the history and origins of the Fatimid Caliph nasab itself. Experts especially historians have different opinions regarding the true origin of the family when associated with Fatima bint Muhammad. When Fatimah with the understanding grand children Ubaydallah al-Mahdi, then naturally people claim that they are descendants of Fatimah bint Muhammad, as well as the descendants of Ali bin Abi Talib. Regardless of whether or not their relationship with the Fatimid Caliph nasab Fatima bint Muhammad and Ali ibn Abi Talib, this caliph is the movement of Shiite Fatimid caliph who basically aspire for a long time and fought tenaciously wanted to form and establish a true government -Right dominated by the Shias on the legitimacy of the descendants of the Prophet himself, as a person entitled to continue the Islamic caliphate